Public finance, security, and development a framework and an application to Afghanistan - Byrd, William A. (World Bank, 2009)
"Security is increasingly viewed as a key condition for economic growth and development. The authors argue that the work and impact of all development partners would be enhanced if the multiple linkages between public finance, security, and development were explicitly taken into account. At the extreme, in some cases better public finance management could have more impact on security than would more troops. The paper first outlines three core linkages between security and development-through the investment climate, human and social capital, and institutions. The authors then propose three complementary tools to analyze the security sector from the point of view of public finance management, service delivery, and governance. This conceptual framework is applied to the case of Afghanistan. The paper closes by drawing some conclusions about possible entry points for dialogue in this difficult area. "--World Bank web site
Includes bibliographical references. - Title from PDF file as viewed on 5/8/2009
Keywords: Economic development -- Afghanistan; Finance, Public -- Afghanistan; Internal security -- Afghanistan